Increasing Public Understanding Through Legal Socialization About Authentic Deeds - Alwi Jaya; Gustika Sandra; Tarmizi Tarmizi (Publikasi Indonesia, 2023)
Deed is something matter which is common found in life public everyday. However unfortunately, society Still Not yet Lots know about deed, esp to deed authentic. Temporary there is a number of deed obeying the law regulation mandatory legislation made in form deed authentic. Based on to background behind the, Proposer in devotion to public This focused to enhancement understanding public through socialization law about deed authentic carried out at the Suara Bone Beradat Legal Dialogue. However because situation Covid- 19 pandemic, so in carry out activity devotion public This done with teleconference method. From activities socialization law This expected public will obtain understanding about deed authentic, as well capable know difference between deed authentic with deed below hand along with with consequence their respective laws.